Assessment of the Growth of Juvenile Oysters Crassostrea tulipa (Lamarck, 1819) in the Coastal Waters of the Gulf of Guinea: Case of the Coastal Lagoon in Southern Benin - Yaovi Zounon; Zacharie Sohou; Manuel Vargas-Yáñez; Dogbè Clément Adjahouinou; Legrand Sylvère Debleo; Théophile Godome; Francina Moya Ruiz; M. Carmen García Martínez (Oceans, 2026)
The coastal zone of the Gulf of Guinea is characterised by the intensive harvesting of Crassostrea tulipa oysters, locally known as ‘Adakpin’ or ‘Atcha’, which serve as a vital source of income for local communities. This study aims to identify the optimal areas, depths, and seasonal periods that favour the growth of juvenile C. tulipa oysters in the coastal lagoon waters of southern Benin. Relatively uniform juvenile oysters were cultured at three depths (surface, mid-water, and bottom) in three production zones (Ahouandji, Dégouè, and Djondji) over the course of one year, covering the four climatic seasons of southern Benin. Juvenile oyster growth (in length, width, height, and weight) was monitored monthly. Simultaneously, key environmental variables (salinity, temperature, pH, water transparency, and dissolved oxygen) were measured in situ to evaluate their influence. A three-way ANOVA revealed that the month of the year had a significant main effect on oyster growth, defining two main growth periods: from October to December 2022 and from March to May 2023. Growth rates decreased during December 2022 to January 2023 and showed no growth from January to March 2023. Growth stopped again from May to September 2023, after the second growth period. Although the main effects of the farming level and production zone were not individually significant, significant two-way interactions were found for ‘Month × Depth’ and ‘Month × Production Zone’. This indicates that the effect of the month on growth depended on both the depth (farming level) and the location (production zone). Survival was highest at the mid-water column (97%) and at the surface (95%). Throughout the study period, survival rates remained consistently high, with the lowest monthly value at or above 80%.

Unusual number of large tectonic earthquakes before and during the birth of the Paricutin monogenetic volcano. Did they trigger, maintain, and boost the volcanic long-lasting activity from 1943 to 1952? - D. Legrand; M. Perton; M.G. Gómez-Vasconcelos; P. Larrea (Journal of South American Earth Sciences, 2026)

Changes in stress revealed by seismic rate changes at El Chichón and Tacaná volcanoes, following the 8 September 2017, Mw8.2 Chiapas, Mexico, earthquake - D. Legrand; M. Perton; R. Campion; L. Peiffer; C. Valdés-González; M. Alatorre-Ibargüengoitia (Journal of South American Earth Sciences, 2026)

GRANDlib: A simulation pipeline for the Giant Radio Array for Neutrino Detection (GRAND) - R. Alves Batista; A. Benoit-Lévy; T. Bister; M. Bohacova; M. Bustamante; W. Carvalho; Y. Chen; L. Cheng; S. Chiche; J.M. Colley; P. Correa; N. Cucu Laurenciu; et al. (Computer Physics Communications, 2025)

Geochemistry of coastal geothermal systems from southern Baja California peninsula (Mexico): Fluid origins, water-rock interaction and tectonics - Loïc Peiffer; Claudio Inguaggiato; Jobst Wurl; John M. Fletcher; Maria Guadalupe Olguín Martínez; Daniel Carbajal Martínez; Denis Legrand; Pablo Hernández-Morales; Carlos E. Reinoza; Boris Chako Tchamabé; Lilia Arana-Salinas; Rodolfo Silva Casarín (Chemical Geology, 2024)

El Chichón volcanic activity before and after the Mw8.2, 2017, Chiapas earthquake, México. Is El Chichón ready to erupt? - D. Legrand; M. Perton; V. López-Landa; S. Ramos; J. Jon Selvas; M. Alatorre-Ibargüengoitia; R. Campion; L. Peiffer; J. L. Macías; G. Cisneros; C. Valdéz; S. De la Cruz-Reyna (Bulletin of Volcanology, 2024)
El Chichón volcano is the most active volcano in the state of Chiapas, México, and experienced its last Plinian eruption (VEI = 5) in 1982. To better assess its volcanic hazard, we studied its readiness to erupt by estimating changes in its internal stress state. These stress changes are difficult to calculate accurately, for example in the absence of focal mechanisms, but their existence can be indirectly revealed by the presence of volcano-tectonic earthquakes, for example following a large tectonic earthquake. We show that the seismic rate recorded at El Chichón volcano increased slightly after the large M w 8.2 Tehuantepec earthquake of 8 September 2017, Chiapas. However, this rate quickly returned to its background level after only 2 months, without any external volcanic manifestations, suggesting that the volcano is not ready to erupt in the near future. Previous observations of slight increases in the volcanic seismicity rate following large earthquakes have been explained by the presence of active hydrothermal systems in the vicinity of the volcano. We propose a similar explanation for El Chichón volcano which is known for its large hydrothermal system. Furthermore, the characteristics of the 2017 seismicity (spatial and magnitude distributions), and the horizontal-to-vertical spectral ratio also confirm the presence of high amounts of water near the volcano. We show that the 2017 volcano-tectonic seismicity is of hydrothermal rather than magmatic origin, in agreement with recent independent geochemical and aeromagnetic studies.

A two-step biosorption methodology for efficient and rapid removal of Fe(II) following As(V) from aqueous solution using abundant biomaterials - K. Richards; A. Garçia; Y.- M. Legrand; C. Grison (International Journal of Environmental Science and Technology, 2023)

Investigating the genetic basis of vertebrate dispersal combining RNA ‐seq, RAD ‐seq and quantitative genetics - Luis M. San‐Jose; Elvire Bestion; Félix Pellerin; Murielle Richard; Lucie Di Gesu; Jordi Salmona; Laurane Winandy; Delphine Legrand; Camille Bonneaud; Olivier Guillaume; Olivier Calvez; Kathryn R. Elmer; et al. (Molecular Ecology, 2023)
Although animal dispersal is known to play key roles in ecological and evolutionary processes such as colonization, population extinction and local adaptation, little is known about its genetic basis, particularly in vertebrates. Untapping the genetic basis of dispersal should deepen our understanding of how dispersal behaviour evolves, the molecular mechanisms that regulate it and link it to other phenotypic aspects in order to form the so‐called dispersal syndromes. Here, we comprehensively combined quantitative genetics, genome‐wide sequencing and transcriptome sequencing to investigate the genetic basis of natal dispersal in a known ecological and evolutionary model of vertebrate dispersal: the common lizard, Zootoca vivipara. Our study supports the heritability of dispersal in semi‐natural populations, with less variation attributable to maternal and natal environment effects. In addition, we found an association between natal dispersal and both variation in the carbonic anhydrase ( CA10 ) gene, and in the expression of several genes ( TGFB2 , SLC6A4 , NOS1 ) involved in central nervous system functioning. These findings suggest that neurotransmitters (serotonin and nitric oxide) are involved in the regulation of dispersal and shaping dispersal syndromes. Several genes from the circadian clock ( CRY2, KCTD21 ) were also differentially expressed between disperser and resident lizards, supporting that the circadian rhythm, known to be involved in long‐distance migration in other taxa, might affect dispersal as well. Since neuronal and circadian pathways are relatively well conserved across vertebrates, our results are likely to be generalisable, and we therefore encourage future studies to further investigate the role of these pathways in shaping dispersal in vertebrates.

Repeated seismic swarms near Paricutin volcano: precursors to the birth of a new monogenetic volcano in the Michoacán-Guanajuato volcanic field, México? - D. Legrand; M. Perton; J. L. Macías; C. Siebe; J. Pacheco; F. Chacón; J. Lermo; L. Quintanar; G. Cisneros (Bulletin of Volcanology, 2023)
The birth of a new monogenetic volcano is difficult to forecast with precision, both in space and time. Nevertheless, seismic activity can alert of the imminence of such an eruption because it usually occurs as small-magnitude earthquake swarms that can last for a few weeks to months prior to an eruption. These swarms are usually related to magma that becomes stalled in the Earth’s crust for variable periods of time before its eventual eruption at the surface. For several reasons, volcanic seismic swarms have rarely been recorded with seismometers before the birth of a new monogenetic volcano. Over the past 25 years, six distinct seismic swarms (in 1997, 1999, 2000, 2006, 2020, and 2021) were detected between Tancítaro and Paricutin volcanoes, in the southwestern part of México’s Michoacán-Guanajuato volcanic field. They are believed to represent repeated attempts of magma to reach the surface hinting that in this region magma might become stalled for some time, so as to not reach the surface in a single ascent event from its source in the mantle. To better understand the magma’s migration path through the crust, we re-located with greater precision some of these seismic swarms by using the same methodology and velocity model to the entire data set. Our results show that these swarms originated within a small area beneath the NE flank of Tancítaro at depths of between 15 and 8 km below sea level (bsl). Apparently, magma is trying to reach the surface within the same conduit network at these crustal depths, but stalls when reaching a depth of ~ 8 km bsl. It is crucial to study these swarms because they might be precursors to a new eruption in this part of the Michoacán-Guanajuato volcanic field. This monogenetic field has been very active, producing several dozen eruptions during the Holocene, the last two Jorullo (1759–1774) and Paricutin (1943–1952). Furthermore, the Tancítaro area displays one of the highest densities of Holocene volcanoes within the entire field, making it a probable candidate location for the birth of a future monogenetic volcano. For these reasons, a permanent seismic network should be installed as soon as possible.

Plant phenology drives seasonal changes in shear stress partitioning in a semi-arid rangeland - Nancy P. Ziegler; Nicholas P. Webb; John A. Gillies; Brandon L. Edwards; George Nikolich; Justin W. Van Zee; Brad F. Cooper; Dawn M. Browning; Ericha M. Courtright; Sandra L. LeGrand (Agricultural and Forest Meteorology, 2023)

Dispersal plasticity driven by variation in fitness across species and environmental gradients - Julie L. M. Campana; Allan Raffard; Alexis S. Chaine; Michèle Huet; Delphine Legrand; Staffan Jacob (Ecology Letters, 2022)
Dispersal plasticity, when organisms adjust their dispersal decisions depending on their environment, can play a major role in ecological and evolutionary dynamics, but how it relates to fitness remains scarcely explored. Theory predicts that high dispersal plasticity should evolve when environmental gradients have a strong impact on fitness. Using microcosms, we tested in five species of the genus Tetrahymena whether dispersal plasticity relates to differences in fitness sensitivity along three environmental gradients. Dispersal plasticity was species‐ and environment‐dependent. As expected, dispersal plasticity was generally related to fitness sensitivity, with higher dispersal plasticity when fitness is more affected by environmental gradients. Individuals often preferentially disperse out of low fitness environments, but leaving environments that should yield high fitness was also commonly observed. We provide empirical support for a fundamental, but largely untested, assumption in dispersal theory: the extent of dispersal plasticity correlates with fitness sensitivity to the environment.

The EMSO Generic Instrument Module (EGIM): Standardized and Interoperable Instrumentation for Ocean Observation - Nadine Lantéri; Henry A. Ruhl; Andrew Gates; Enoc Martínez; Joaquin del Rio Fernandez; Jacopo Aguzzi; Mathilde Cannat; Eric Delory; Davide Embriaco; Robert Huber; Marjolaine Matabos; George Petihakis; et al. (Frontiers in Marine Science, 2022)
The oceans are a fundamental source for climate balance, sustainability of resources and life on Earth, therefore society has a strong and pressing interest in maintaining and, where possible, restoring the health of the marine ecosystems. Effective, integrated ocean observation is key to suggesting actions to reduce anthropogenic impact from coastal to deep-sea environments and address the main challenges of the 21st century, which are summarized in the UN Sustainable Development Goals and Blue Growth strategies. The European Multidisciplinary Seafloor and water column Observatory (EMSO), is a European Research Infrastructure Consortium (ERIC), with the aim of providing long-term observations via fixed-point ocean observatories in key environmental locations across European seas from the Arctic to the Black Sea. These may be supported by ship-based observations and autonomous systems such as gliders. In this paper, we present the EMSO Generic Instrument Module (EGIM), a deployment ready multi-sensor instrumentation module, designed to measure physical, biogeochemical, biological and ecosystem variables consistently, in a range of marine environments, over long periods of time. Here, we describe the system, features, configuration, operation and data management. We demonstrate, through a series of coastal and oceanic pilot experiments that the EGIM is a valuable standard ocean observation module, which can significantly improve the capacity of existing ocean observatories and provides the basis for new observatories. The diverse examples of use included the monitoring of fish activity response upon oceanographic variability, hydrothermal vent fluids and particle dispersion, passive acoustic monitoring of marine mammals and time series of environmental variation in the water column. With the EGIM available to all the EMSO Regional Facilities, EMSO will be reaching a milestone in standardization and interoperability, marking a key capability advancement in addressing issues of sustainability in resource and habitat management of the oceans.

Seismic evidence of the active regional tectonic faults and the Copahue volcano, at Caviahue Caldera, Argentina - V. M. Montenegro; S. Spagnotto; D. Legrand; A. T. Caselli (Bulletin of Volcanology, 2021)

Regional integration of long-term national dense GNSS network solutions - Ambrus Kenyeres; J. G. Bellet; C. Bruyninx; A. Caporali; F. de Doncker; B. Droscak; A. Duret; P. Franke; I. Georgiev; R. Bingley; L. Huisman; L. Jivall; et al. (GPS Solutions, 2019)
The EUREF Permanent Network Densification is a collaborative effort of 26 European GNSS analysis centers providing series of daily or weekly station position estimates of dense national and regional GNSS networks, in order to combine them into one homogenized set of station positions and velocities. During the combination, the station meta-data, including station names, DOMES numbers, and position offset definitions were carefully homogenized, position outliers were efficiently eliminated, and the results were cross-checked for any remaining inconsistencies. The results cover the period from March 1999 to January 2017 (GPS week 1000-1933) and include 31 networks with positions and velocities for 3192 stations, well covering Europe. The positions and velocities are expressed in ITRF2014 and ETRF2014 reference frames based on the Minimum Constraint approach using a selected set of ITRF2014 reference stations. The position alignment with the ITRF2014 is at the level of 1.5, 1.2, and 3.2 mm RMS for the East, North, Up components, respectively, while the velocity RMS values are 0.17, 0.14, and 0.38 mm/year for the East, North, and Up components, respectively. The high quality of the combined solution is also reflected by the 1.1, 1.1, and 3.5 mm weighted RMS values for the East, North, and Up components, respectively.

Challenging exploration of troubled waters: a decade of surveys of the giant freshwater pearl mussel Margaritifera auricularia in Europe - Vincent Prié; Joaquin Soler; Rafael Araujo; Xavier Cucherat; Laurent Philippe; Nicolas Patry; Benjamin Adam; Nicolas Legrand; Philippe Jugé; Nina Richard; Karl M. Wantzen (Hydrobiologia, 2018)

Indigenous arthropod natural enemies of the invasive brown marmorated stink bug in North America and Europe - Paul K. Abram; Kim A. Hoelmer; Angelita Acebes-Doria; Heather Andrews; Elizabeth H. Beers; J. Christopher Bergh; Ric Bessin; David Biddinger; Paul Botch; Matthew L. Buffington; Mary L. Cornelius; Elena Costi; et al. (Journal of Pest Science, 2017)

Assessment of changes in atmospheric dynamics and dust activity over southwest Asia using the Caspian Sea–Hindu Kush Index - D. G. Kaskaoutis; A. Rashki; E. E. Houssos; M. Legrand; P. Francois; A. Bartzokas; H. D. Kambezidis; U. C. Dumka; D. Goto; T. Takemura (International Journal of Climatology, 2017)
This study examines the influence of the Caspian Sea–Hindu Kush Index ( CasHKI ) on local and synoptic meteorology as well as on dust emissions over southwest ( SW ) Asia by means of National Center for Environmental Prediction/National Center for Atmospheric Research ( NCEP‐NCAR ) re‐analysed mean sea‐level pressure ( MSLP ), geopotential height at 700 hPa and surface meridional wind, along with meteorological data at Zabol, east Iran and Meteosat/Infrared Difference Dust Index (IDDI) retrievals. The analysis focuses on the summer period (June to September) of 2000–2014 and the winter period (November to March) of 1963–2014. The CasHKI values are mostly controlled by the MSLP anomalies over the Caspian Sea (CS) domain, varying from approximately −25 to +35 hPa in winter and from approximately−10 to +14 hPa in summer, but without a clear annual pattern. The CasHKI values are classified into four modes for each month depending on their intensity. In the summer months, the high CasHKI mode is associated with enhanced MSLP over central Asia and deepening of the Indo‐Pakistan thermal low associated with the Indian summer monsoon. At 700‐hPa level, the high CasHKI mode shows an enhancement of the Arabian ridge, expanding it to the north over Iran and the CS, with a concurrent strengthening of the Indian trough, leading to intensification of northerly winds along east Iran. This results in significant increase in dust activity over SW Asia, which is also apparent in the winter months. Furthermore, the intensification of the northerly flow associated with the high CasHKI modes drops the temperature and increases the relative humidity over Zabol, especially during winter. The SPRINTARS ‐model simulations also show increased dust emissions and concentrations for the high CasHKI values, confirming that the CasHKI variations modulate the dust activity over SW Asia throughout the year.

Effects of in situ CO2 enrichment on Posidonia oceanica epiphytic community composition and mineralogy - T. E. Cox; M. Nash; F. Gazeau; M. Déniel; E. Legrand; S. Alliouane; P. Mahacek; A. Le Fur; J.-P. Gattuso; S. Martin (Marine Biology, 2017)

Erratum to: Influence of different GPS receiver antenna calibration models on geodetic positioning - Q. Baire; C. Bruyninx; J. Legrand; E. Pottiaux; W. Aerts; P. Defraigne; N. Bergeot; J. M. Chevalier (GPS Solutions, 2016)

Uncertainty estimation for operational ocean forecast products—a multi-model ensemble for the North Sea and the Baltic Sea - Inga Golbeck; Xin Li; Frank Janssen; Thorger Brüning; Jacob W. Nielsen; Vibeke Huess; Johan Söderkvist; Bjarne Büchmann; Simo-Matti Siiriä; Olga Vähä-Piikkiö; Bruce Hackett; Nils M. Kristensen; et al. (Ocean Dynamics, 2015)

Meteorological aspects associated with dust storms in the Sistan region, southeastern Iran - D. G. Kaskaoutis; A. Rashki; E. E. Houssos; A. Mofidi; D. Goto; A. Bartzokas; P. Francois; M. Legrand (Climate Dynamics, 2015)

Influence of different GPS receiver antenna calibration models on geodetic positioning - Q. Baire; C. Bruyninx; J. Legrand; E. Pottiaux; W. Aerts; P. Defraigne; N. Bergeot; J. M. Chevalier (GPS Solutions, 2014)

Isolation and characterization of 15 microsatellite loci in the specialist butterfly Boloria eunomia - Delphine Legrand; Audrey Chaput-Bardy; Camille Turlure; Quentin Dubois; Michèle Huet; Nicolas Schtickzelle; Virginie M. Stevens; Michel Baguette (Conservation Genetics Resources, 2014)

In vitro antibacterial activity of doripenem against clinical isolates from French teaching hospitals: proposition of zone diameter breakpoints - C. Lascols; P. Legrand; A. Mérens; R. Leclercq; L. Armand-Lefevre; H. B. Drugeon; M. D. Kitzis; C. Muller-Serieys; M. E. Reverdy; M. Roussel-Delvallez; C. Moubareck; A. Lemire; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2011)

O-methyltransferase(s)-suppressed plants produce lower amounts of phenolic vir inducers and are less susceptible to Agrobacterium tumefaciens infection - Stéphane Maury; A. Delaunay; F. Mesnard; D. Crônier; B. Chabbert; P. Geoffroy; M. Legrand (Planta, 2010)

Materno-fetal transmission of human coronaviruses: a prospective pilot study - A. Gagneur; E. Dirson; S. Audebert; S. Vallet; M. C. Legrand-Quillien; Y. Laurent; M. Collet; J. Sizun; E. Oger; C. Payan (European Journal of Clinical Microbiology & Infectious Diseases, 2008)

Acyltransferase-catalysed p- coumarate ester formation is a committed step of lignin biosynthesis - L Hoffmann; S Besseau; P Geoffroy; C Ritzenthaler; D Meyer; C Lapierre; B Pollet; M Legrand (Plant Biosystems, 2005)

A particular hepatitis C virus protease NS3 gene pattern in a patient not responding to interferon-ribavirin therapy - S. Vallet; J. B. Nousbaum; S. Gouriou; M. C. Legrand-Quillien; A. Goudeau; B. Picard (European Journal of Clinical Microbiology & Infectious Diseases, 2005)

Campylobacter fetus meningitis in a diabetic adult cured by imipenem - J. Herve; N. Aissa; P. Legrand; M. Sorkine; M.J. Calmette; A. Santin; E. Roupie; B. Renaud (European Journal of Clinical Microbiology & Infectious Diseases, 2004)

The European Gravity Field and Steady-State Ocean Circulation Explorer Satellite Mission Its Impact on Geophysics - J. A. Johannessen; G. Balmino; C. Le Provost; R. Rummel; R. Sabadini; H. Sünkel; C.C. Tscherning; P. Visser; P. Woodworth; C. Hughes; P. Legrand; N. Sneeuw; et al. (Surveys in Geophysics, 2003)

Multicenter Evaluation of an Automated System Using Selected Bacteria That Harbor Challenging and Clinically Relevant Mechanisms of Resistance to Antibiotics - R. Leclercq; M.- Nicolas-Chanoine; P. Nordmann; A. Philippon; P. Marchais; A. Buu-Hoï; H. Chardon; H. Dabernat; F. Doucet-Populaire; C. Grasmick; P. Legrand; C. Muller-Serieys; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2001)

Interpretation of Ni2p XPS spectra of Ni conductors and Ni insulators - H. W. Nesbitt; D. Legrand; G. M. Bancroft (Physics and Chemistry of Minerals, 2000)

Seasonal abundance and toxicity of the dinoflagellate Gambierdiscus spp. (Dinophyceae), the causative agent of ciguatera in Tahiti, French Polynesia - M. Chinain; M. Germain; X. Deparis; S. Pauillac; A.-M. Legrand (Marine Biology, 1999)

Cyamemazine decreases ethanol intake in rats and convulsions during ethanol withdrawal syndrome in mice - Mickal Naassila; Elisabeth Legrand; Franoise d'Alche-Bire; M. Daoust (Psychopharmacology, 1998)

Mapping of the galectin-3 gene (LGALS3) to human Chromosome 14 at region 14q21-22 - J. Raimond; D. B. Zimonjic; C. Mignon; M. -G. Mattei; N. C. Popescu; M. Monsigny; A. Legrand (Mammalian Genome, 1997)

Genetic variability in wild cherry populations in France. Effects of colonizing processes - S. Mariette; M. Lefranc; P. Legrand; D. Taneyhill; N. Frascaria-Lacoste; N. Machon (Theoretical and Applied Genetics, 1997)

Subcellular localization of acidic and basic PR proteins in tobacco mosaic virus-infected tobacco - Isabelle Dore; M. Legrand; B. J. C. Cornelissen; J. F. Bol (Archives of Virology, 1991)